Testing Clean-Up Methods for the Quantification of Monosaccharides and Uronic Acids - Irene Bargagli; Francesca Sabatini; Francesca Modugno; Jeannette Jacqueline Łucejko (Applied Sciences, 2022)
The determination of carbohydrate composition is extremely important for quality control in food and beverages, in material science, in pharmaceutics, and in the field of cultural heritage. Considering the complexity and the heterogeneity of the matrices, the optimization of extraction and purification steps aiming at maximizing the saccharide recovery from the matrix and effectively removing interferences is mandatory. The presence of inorganic components, besides being detrimental to the analytical instrumentation, can catalyze the isomerization of some sugars causing an alteration to their quantitative and qualitative profiles. In the present paper, protocols for suppressing the interference of inorganic ions in the quantification of monosaccharides and uronic acids by Gas Chromatography–Mass Spectrometry (GC-MS) are proposed. Two clean-up methods based on ion exchange resins (Amberlite MB-6113 and Amberlite IRN-150) and one making use of solid-phase extraction with a polypropylene Solid-Phase Extraction (SPE) column were tested on a standard carbohydrate solution, and the elution conditions optimized. The best purification conditions, in terms of higher recovery yield values for seven monosaccharides and two uronic acids, were obtained using SPE. Furthermore, the optimized SPE method was validated on a sample of mural painting rich in saccharides and inorganic material.